Criminal Acts in Completing Early Marriage Requirements: Tuku Umur Practices in Islamic Communities in Central Java, Indonesia - Ismawayati, Any; Ngazizah, Inna Fauziatal (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The goal of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 Concerning Marriage is to reduce the high rate of early marriage because it violates the rights and development of children. In fact, the rate of child marriage in Indonesia is rising. This circumstance raises the question of whether or not the current regulations are effective. This study seeks to determine the extent to which the Islamic community in Central Java understands the significance of the age limit for marriage. This study also determines why the Islamic community in Central Java prefers